Endocarditis infecciosa sobre válvula mitral nativa de alto riesgo embólico - Moreno-Martínez, Francisco L.; Marrero Falcón, Carmen G.; San Narciso de la Rosa, Jaime; Gómez Guindal, José A. (CorSalud, 2021)
Endocarditis infecciosa sobre válvula mitral nativa de alto riesgo embólico